Zoonotic pathogens associated with Hyalomma aegyptium in endangered tortoises: evidence for host-switching behaviour in ticks? - Paștiu, Anamaria I (BioMed Central, 2012)
BACKGROUND: Hyalomma aegyptium is a hard-tick with a typical three-host life cycle. The main hosts are Palearctic tortoises of genus Testudo. However, other hosts can be used by immature ticks for feeding in natural conditions. Given this complex ecology and multiple host use, the circulation of pathogens by H. aegyptium between various hosts can be important from epidemiological point of view. The aim of this study was to evaluate the role of H. aegyptium as natural carrier of four important zoonotic pathogens. METHODS: From 2008 to 2011, 448 H. aegyptium ticks were collected from 45 Spur-thighed tortoises, Testudo graeca in Romania. DNA was extracted individually from each tick using a commercial kit. DNA was examined for the presence of specific sequences of Borrelia burgdorferi s.l., Anaplasma phagocytophilum, Ehrlichia canis and Coxiella burnetii by PCR, according to previously described protocols. RESULTS: PCR analysis of H. aegyptium revealed the presence of A. phagocytophilum (18.8%), E. canis (14.1%) and C. burnetii (10%). 32.4% of the ticks were infected with at least one pathogen and 9.8% had co-infections. The stages most frequently infected were nymphs (50%) followed by males (33.9%) and females (27%). The number of tortoises which harboured infected ticks was 27/45 examined (60%). From all tested T. graeca, 40% harboured ticks infected with A. phagocytophilum, 46.7% had ticks infected with E. canis and 33.3% had ticks with C. burnetii. This study reports for the first time the presence of A. phagocytophilum and E. canis in H. aegyptium. CONCLUSIONS: The presence and relatively high prevalence of three important zoonotic pathogens in H. aegyptium raises the question of their epidemiologic importance in disease ecology. As tortoises are unlikely to be reservoir hosts for A. phagocytophilum and E. canis and both these pathogens are common in H. aegyptium, this is an important indication for (1) a possible increased host-switching behaviour of these ticks to competent reservoir hosts (i.e. hedgehogs) and (2) transstadial transmission. Furthermore, if we consider also the presence of C. burnetii, we conclude that T. graeca and its ticks should be evaluated more seriously when assessing the eco-epidemiology of zoonotic diseases.